Effect of berberine associated with photodynamic therapy in cell lines - Oliveira, P. M.; Lopes, T. Z. [UNESP]; Tedesco, A. C.; Rahal, P. [UNESP]; Calmon, M. F. [UNESP] (Elsevier, 2020)
Cervical cancer is a serious worldwide health problem. In view of the potentially harmful effects of current conventional therapies, photodynamic therapy may be an option as it is a minimally invasive therapy and can promote selective cytotoxic activity for neoplastic cells in the target tissue., Berberine (BBR) as an isolated molecule is a natural compound that has antineoplastic properties and potential action as a photosensitizer agent. The purpose of this study was to evaluate the use of berberine as a photosensitizer in photodynamic therapy (PDT) protocols and observe the effects produced by this association in cervical carcinoma cells and in immortalized keratinocytes. Incubation with 2.5 μM berberine promoted less than 10 % of cellular death in both cell lines studied. In addition, by fluorescence microscopy, we demonstrated that berberine was internalized by the cells, and after a period of 48 h, it was still present in the intracellular environment preferentially localized in the cytoplasm. After photodynamic therapy using berberine as a photosensitizer and visible light activation at 447 (±10) nm, we observed a phototoxic effect, which resulted in 19.84 % cell viability for Caski cells and 47.22 % cell viability for HaCaT. Treatment with berberine associated with photodynamic therapy promoted an increase in the production of reactive species of oxygen (ROS) and caspase-3 activity, indicating a preferential cell death mechanism by caspase-dependent apoptosis. Therefore, we demonstrated that berberine is an efficient photosensitizer and that its association with photodynamic therapy may be a potential anticancer treatment strategy for cervical cancer.
Keywords: Berberine; Cell death; Cervical cancer; Natural compound; Photodynamic therapy